The Effect of Electronic Word of Mouth and Brand Image on Online Shopping Behavior Through Online Purchase Intention as Intervening Variables (Study on Marketplace Shopee Users) - Gabriella Stefanny; Heri Pratikto; Agus Hermawan (CV. AFDIFAL MAJU BERKAH, 2022)
Electronic word of mouth (E-Wom) is currently something that is needed and is considered by consumers before choosing to use or consume something. In addition to e-wom, consumers also consider the image of a company. The better the company's image and positive reviews, the more it will make consumers believe in consuming or using a brand. This study aims to determine the effect of e-wom and brand image on online shopping behavior through online purchase intention on Shopee users. This research is quantitative research with the help of SPSS 22 software. The population in this study is Shopee application users. The sample in this study was 200 respondents. In addition, to test the feasibility of the instrument, validity and reliability tests were used, and classical assumption tests, hypothesis testing, and path analysis methods were used. The results showed that (1) e-wom has a positive and significant influence on online shopping behavior, and (2) e-wom has a positive and significant influence on online purchase intention. (3) brand image has positive and significant influence on online shopping behavior, (4) brand image has a positive and significant influence on online purchase intention, and (5) online purchase intention has a positive and significant influence on online shopping behavior, (6) e-wom has a positive and significant influence on online shopping behavior through online purchase intention, and (7) brand image has a positive and significant influence on online shopping behavior through online purchase intention.